Enzyme use in kibble diets formulated with wheat bran for dogs: Effects on processing and digestibility - Sá, F. C. [UNESP]; Vasconcellos, R. S.; Brunetto, M. A.; Filho, F. O R [UNESP]; Gomes, M. O S [UNESP]; Carciofi, A. C. [UNESP] (Wiley, 2013)
Recently, there is an interest in technologies that favour the use of coproducts for animal nutrition. The effect of adding two enzyme mixtures in diets for dogs formulated with wheat bran (WB) was evaluated. Two foods with similar compositions were formulated: negative control (NC; without WB) and test diet (25% of WB). The test diet was divided into four treatments: without enzyme (positive control), enzyme mixture 1 (ENZ1; added before extrusion β-glucanase, xylanase, cellulase, glucoamylase, phytase); enzyme mixture 2 (ENZ2; added before extrusion the ENZ1 more α-amylase); enzyme mixture 2 added after the extrusion (ENZ2ex). ENZ1 and ENZ2 were used to evaluate the enzyme effect on extruder pre-conditioner (processing additive) and ENZ2ex to evaluate the effect of enzyme supplementation for the animal. Digestibility was measured through total collection of faeces and urine. The experiment followed a randomized block design with five treatments (diets) and six dogs per diet, totalling 30 dogs (7.0 ± 1.2 years old and 11.0 ± 2.2 kg of body weight). Data were submitted to analysis of variance and means compared by Tukey's test and orthogonal contrasts (p < 0.05). Reducing sugars showed an important reduction after extrusion, suggesting the formation of carbohydrate complexes. The apparent total tract digestibility (ATTD) of dry matter, organic matter, crude protein, acid-hydrolysed fat and energy was higher in NC than in diets with WB (p < 0.001), without effects of enzyme additions. WB diets resulted in higher faecal production and concentration of short-chain fatty acids (SCFA) and reduced pH and ammonia concentration (p < 0.01), with no effect of enzyme addition. The enzyme addition did not result in improved digestibility of a diet high in non-starch polysaccharides; however, only ATTD was measured and nutrient fermentation in the large intestine may have interfered with the results obtained. WB modified fermentation product formation in the colon of dogs. © 2013 Blackwell Verlag GmbH.
Keywords: Amylase; Butyrate; Dietary fibre; Glucanase; Non-starch polysaccharide; Reducing sugars